2013
DOI: 10.3892/etm.2013.1094
|View full text |Cite
|
Sign up to set email alerts
|

Mucinous cystadenocarcinoma of the appendix in which contrast-enhanced ultrasonography was useful for assessing blood flow in a focal nodular lesion in the tumor cavity: A case report

Abstract: A 63-year-old woman was admitted to hospital with pain in the right lower quadrant. Abdominal computed tomography (CT) revealed a 60-mm cystic mass at a site corresponding to the appendix. The mass wall on the appendicular ostium was thickened and enhanced by contrast, while calcification was observed in the mass wall on the appendicular tip. No projection was observed in the mass cavity. On abdominal ultrasonography (US), the mass wall on the appendicular ostium was thickened and projections were observed at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…In two mucinous cystadenocarcinomas, cystic dilatation of the appendix (mucocele) with irregular wall thickening was seen on sonography, which correlated with pathologic findings. These findings were consistent with those of a previous study,[ 12 14 15 ] which reported that when cystic dilatation of the appendix is present, wall irregularity and internal soft-tissue density with nodular thickening are associated with malignancy on CT. On the other hand, five nonmucinous carcinomas (four adenocarcinomas and one signet-ring cell carcinoma) had relatively small inner luminal diameters and thickened appendiceal walls ( n = 4) or mass ( n = 1) combined with submucosal hypoechogenicity. According to a previous report,[ 16 17 18 19 20 ] malignant tumors of the colon demonstrated the following wall characteristics on a high-resolution sonographic examination: heterogeneous hypoechoic mass, irregular wall thickening, and absence of a layered appearance of the wall.…”
Section: Discussionsupporting
confidence: 93%
“…In two mucinous cystadenocarcinomas, cystic dilatation of the appendix (mucocele) with irregular wall thickening was seen on sonography, which correlated with pathologic findings. These findings were consistent with those of a previous study,[ 12 14 15 ] which reported that when cystic dilatation of the appendix is present, wall irregularity and internal soft-tissue density with nodular thickening are associated with malignancy on CT. On the other hand, five nonmucinous carcinomas (four adenocarcinomas and one signet-ring cell carcinoma) had relatively small inner luminal diameters and thickened appendiceal walls ( n = 4) or mass ( n = 1) combined with submucosal hypoechogenicity. According to a previous report,[ 16 17 18 19 20 ] malignant tumors of the colon demonstrated the following wall characteristics on a high-resolution sonographic examination: heterogeneous hypoechoic mass, irregular wall thickening, and absence of a layered appearance of the wall.…”
Section: Discussionsupporting
confidence: 93%
“…Because dystrophic calcification co-exists either with non-neoplastic diverticula or neoplasms, psammomatous calcification is observed only in neoplastic group. Soft tissue mass with curvilinear calcifications in the right lower quadrant detected with abdominal radiographs is a significant finding with regard to LGMN diagnosis [1,23,24]. In LGMNs, calcifications in the wall may be confirmed histopathologically.…”
Section: Discussionmentioning
confidence: 80%
“…(E) The increase in the echogenicity in the Tx group was more prominent at POD 56 than at POD 14. was used to detect liver tumors in animal models (24,25) and in the clinic (26). Currently, the second-generation contrast agent, Sonazoid 1 (NC100100), is widely used to detect many types of gastroenterological tumor (27)(28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%